Approach an appropriate decision on fetus with endocardial fibroelastosis in collaboration with cardiovascular profile score: A case report. Issue 30 (July 2016) - Yan, Hualin; Zhou, Kaiyu; Zhang, Zhang; Wang, Chuan; Guo, Nan; Li, Yifei; Hua, Yimin
Abstract: Introduction: Fetal endocardial fibroelastosis (EFE) is a kind of rare fetal cardiac malformation characterized by the diffuse thickening of the ventricular endocardium. The diagnosis of fetal EFE depends on the echocardiographic features which are still confused that how to make an appropriate pregnant decision due to the conflict between high prenatal mortality and acceptable prognosis once after birth. Here, we seriously built a 4-gradation recommendation system based on cardiovascular profile score (CVPS) to supply a prediction of clarified pregnant outcomes with EFE and provide a practical way to offer optimal medical consultation. Clinical procedure: A suspected case of fetal EFE has been aware at 24th gestational week by fetal echocardiography. The CVPS of this affected fetus dropped to 6 out of 10 points, which indicated a severe heart condition along with the fetus and predicted an adverse fetal prognosis according to our recommendation system. After fully informed consent, the prospective parents determined to terminate pregnancy. Following the induced abortion, postmortem pathological findings confirmed the echocardiographic suspicion of EFE. Conclusion: According to our experience and previous researches, we could reach a relative clear prediction of the outcomes of the EFE fetuses based on the CVPS of such suspected fetuses, which should lead to approach an appropriate pregnant decision for such fetuses.